If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying h(x) = (2x + -6) Multiply h * x hx = (2x + -6) Reorder the terms: hx = (-6 + 2x) Remove parenthesis around (-6 + 2x) hx = -6 + 2x Solving hx = -6 + 2x Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Divide each side by 'x'. h = -6x-1 + 2 Simplifying h = -6x-1 + 2 Reorder the terms: h = 2 + -6x-1
| 28-0.3=0.74-12 | | 9(w-6)= | | 8w^2-2122w+20000=0 | | 2d+4=10+6d | | 11-7*2+3= | | x*.16=4 | | (x^3)+(5x^2)-x-5=0 | | 8/7y-4/7 | | 8x+10=6x-12 | | x*.15=3 | | 4c=2c+9 | | 7.37x+64=54.3169+8x | | 6/7x-3/7=9 | | 6.95x+34.75=69.5 | | 99-w=208 | | 8.6a+11=114.2 | | 21=8d-9(2d+1) | | x^2+14x-106=0 | | 10/11x-2/11=5 | | 9x(7-4)*2+9= | | 22.5=6.3w+1.2w | | -3*1/6y-18=72 | | 4x-2+1=15 | | 2z=z-3 | | 110+58=y | | 1-3(n+5)=-4 | | -10=5w+5 | | z-3=9z+53 | | 49*2-4(Y+11)=3Y-2 | | V^2-18v+49=-3 | | 5+21x=2x+27 | | 0.06(1000-x)+.10x=80 |